PENGARUH PENJUALAN TERHADAP LABA KOTOR PADA PT KALBE FARMA TBK PERIODE 2015-2019 (SURVEI PADA BURSA EFEK INDONESIA) - Dian Candra Fatihah; Anjani Pratiwi; Ai Nunung (EKBIS (Ekonomi & Bisnis), 2022)
THE EFFECT OF SALES ON GROSS PROFIT IN PT KALBE FARMA TBK 2015-2019 PERIOD (SURVEY ON THE INDONESIA STOCK EXCHANGE) Abstract This research was aimed to determine the influence of sales to the gross profit at PT Kalbe Farma Tbk period 2015-2019. The method used in this research was quantitative method. The data collection techniques were done by literature study, documentation, and browses from the internet. The data analysis techniques were done by normality test, correlation coefficient, coefficient of determination, simple linier regression analysis, and hypothesis test. From this research, the correlation coefficient results obtained by 0,947 this means that this had a positive relationship with the level of relationship is very strong, and the coefficient determination was 89,7% this shows the influence of sales to the gross profit and the rest 10,3% was influence by others factors that not examined. The t test result obtained 5,110 > 3,182 (tcount > ttable), so Ho was rejected and Ha was accepted which means there was a significant influence between sales and the gross profit. The advice given are, staying consistent in increasing sales by developing creative innovations on products or management strategies, pay more attention to the calculation of cost of goods sold, and more streamline the production cost by minimizing the expenditure cost. Keywords : Sales, Gross Profit